2011
DOI: 10.1126/science.1208130
|View full text |Cite
|
Sign up to set email alerts
|

The Mutational Landscape of Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a common, morbid, and frequently lethal malignancy. To uncover its mutational spectrum, we analyzed whole-exome sequencing data from 74 tumor-normal pairs. The majority exhibited a mutational profile consistent with tobacco exposure; human papilloma virus was detectable by sequencing of DNA from infected tumors. In addition to identifying previously known HNSCC genes (TP53, CDKN2A, PTEN, PIK3CA, and HRAS), the analysis revealed many genes not previously implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

136
2,428
15
15

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 2,239 publications
(2,594 citation statements)
references
References 61 publications
136
2,428
15
15
Order By: Relevance
“…In 2011, two independent studies about mutational landscape of HNSCC revealed that NOTCH is frequently mutated in HNSCC 6, 7. By whole‐exome sequencing of 74 HNSCC tumor‐normal pairs 6, mutations of NOTCH1 , NOTCH2 , and NOTCH3 were identified in 14%, 5%, and 4% of HNSCC samples.…”
Section: Notch Signaling In Head and Neck Squamous Cell Carcinoma (Hnmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2011, two independent studies about mutational landscape of HNSCC revealed that NOTCH is frequently mutated in HNSCC 6, 7. By whole‐exome sequencing of 74 HNSCC tumor‐normal pairs 6, mutations of NOTCH1 , NOTCH2 , and NOTCH3 were identified in 14%, 5%, and 4% of HNSCC samples.…”
Section: Notch Signaling In Head and Neck Squamous Cell Carcinoma (Hnmentioning
confidence: 99%
“…By whole‐exome sequencing of 74 HNSCC tumor‐normal pairs 6, mutations of NOTCH1 , NOTCH2 , and NOTCH3 were identified in 14%, 5%, and 4% of HNSCC samples. In an independent exome‐sequencing study of 32 HNSCC primary tumors 7, NOTCH1 somatic mutations were identified in 15% of patients, and following TP53, NOTCH1 was identified as the second most frequently mutated gene.…”
Section: Notch Signaling In Head and Neck Squamous Cell Carcinoma (Hnmentioning
confidence: 99%
See 3 more Smart Citations